2014 19th Asia and South Pacific Design Automation Conference (ASP-DAC) 2014
DOI: 10.1109/aspdac.2014.6742935
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and inexpensive performance monitoring for variability-aware systems

Abstract: Abstract-Designing reliable integrated systems has become a major challenge with shrinking geometries, increasing fault rates and devices which age substantially in their usage life. The proposed research is motivated by the observation that many of the in-field failures are delay failures and several variability signatures are also delay-related. The origins of temporal delay fluctuations include manufacturing variability, voltage/temperature changes, negative or positive bias temperature instability-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Using ARM Cortex M3-based "Red Cooper" test chips manufactured in a 45nm SOI technology [15] as part of the NSF Variability Expedition (variability.org), we ran March SS tests [11] on the SRAM memory to characterize the nature of bit faults as VDD is reduced. We observed that in the presence of process variation, SRAM faults caused by voltage scaling obey the so-called fault inclusion property, i.e., bits that fail at some supply voltage level will also fail at all lower voltages.…”
Section: Introductionmentioning
confidence: 99%
“…Using ARM Cortex M3-based "Red Cooper" test chips manufactured in a 45nm SOI technology [15] as part of the NSF Variability Expedition (variability.org), we ran March SS tests [11] on the SRAM memory to characterize the nature of bit faults as VDD is reduced. We observed that in the presence of process variation, SRAM faults caused by voltage scaling obey the so-called fault inclusion property, i.e., bits that fail at some supply voltage level will also fail at all lower voltages.…”
Section: Introductionmentioning
confidence: 99%
“…The NSF Variability Expedition ( Figure 5) [49] seeks to build opportunistic computing systems where hardware variations are monitored and exposed to software layers (instead of being hidden behind pessimistic margins) enabling adaptations. The work has spanned circuit-level monitoring and test (e.g., [50], [51], [60]), variability emulation ( [52], [53]), runtime for embedded systems (e.g., [54], [55]), GPUs (e.g., [56], [48]), processors (e.g., [56], [58]), memories (e.g., [55], [64], [59]) and storage (e.g., [61], [62]). In the following, we briefly describe some of the research on memory variability done under the Variability Expedition.…”
Section: Variability Expeditionmentioning
confidence: 99%